2021
DOI: 10.1021/acsami.0c21630
|View full text |Cite
|
Sign up to set email alerts
|

Contradiction or Unity? Thermally Stable Fluorescent Probe for In Situ Fast Identification of Self-sort or Co-assembly of Multicomponent Gelators with Sensitive Properties

Abstract: Analyzing the assembly patterns of multicomponent gelators is important for understanding their assembly rules and precisely manipulating their molecular structure to form a tailored multifunctional supramolecular gel. But the fast in situ recognition technology to infer whether the assembly pattern is a self-sorting or co-assembled system is lacking. For developing a widely applicable stable and sensitive fluorescent probe to infer assembly patterns, we design and synthesize the multiple peripheral functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Except for chemical analyst, the physical signals, such as force, temperature, and light, can also be effectively detected by organosilicon-based chemosenosrs [ 61 , 69 , 80 , 81 , 82 ]. Heras et al reported carbazole-containing polysiloxane elastomers (LSCEs) to detect mechanical events by recording fluorescent signals [ 83 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Except for chemical analyst, the physical signals, such as force, temperature, and light, can also be effectively detected by organosilicon-based chemosenosrs [ 61 , 69 , 80 , 81 , 82 ]. Heras et al reported carbazole-containing polysiloxane elastomers (LSCEs) to detect mechanical events by recording fluorescent signals [ 83 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Wang Xu's group 80 recently developed an in situ recognition technology to distinguish the assembly mode of multicomponent gels and determine whether it is self‐sorting assembly or co‐assembly. They designed and synthesized multiple peripheral functional groups (TPE) to modify a well‐defined cubic core (POSS) three‐dimensional dendrimer.…”
Section: Applicationmentioning
confidence: 99%
“…In recent years, supramolecular self-assembled materials have drawn immense attention in biological imaging, analyte detection, and sensing applications. Common fluorescent supramolecular sensors include polymers, gels, films, self-assembled nanomaterials, and so on. Each sensor has its own strengths in some way.…”
Section: Introductionmentioning
confidence: 99%